2010
DOI: 10.1111/j.1439-0426.2010.01608.x
|View full text |Cite
|
Sign up to set email alerts
|

A histological study of the organogenesis of the digestive system in bay snook Petenia splendida Günther, 1862 from hatching to the juvenile stage

Abstract: In bay snook (Petenia splendida) larvae the histological development of the digestive system and swim bladder, and their relative timing of differentiation were studied from hatching to 45 days post-hatch (dph) at 29°C. Newly hatched larvae showed a simple digestive tract, which appeared as a straight undifferentiated tube lined by a single layer of columnar epithelial cells (future enterocytes). The anatomical and histological differentiation of the digestive tract and accessory glands was a very intense, asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
22
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 36 publications
7
22
1
4
Order By: Relevance
“…Time shifts between pepsin activity and morphological development of gastric glands have also been observed in other species such as California halibut P. californicus (Á lvarez-González et al 2006), white seabass A. nobilis (Galaviz et al 2011), spotted rose snapper L. guttatus (Galaviz et al 2012) and Asian sea bass L. calcarifer (Srichanun et al 2013). The time sequence of gastric gland appearance and the maturation of the stomach vary among families, species and their reproductive guilds (Falk-Petersen 2005;Treviño et al 2011). In the present study, an increase in pepsinogen gene expression was first observed at 14-16 dph, while the increase in pepsin activity was first observed at 20-24 dph, coinciding with the formation of the stomach as an extension of the esophagus, showing a relationship between the synthesis of the precursor and the production of pepsin.…”
Section: Discussionmentioning
confidence: 89%
“…Time shifts between pepsin activity and morphological development of gastric glands have also been observed in other species such as California halibut P. californicus (Á lvarez-González et al 2006), white seabass A. nobilis (Galaviz et al 2011), spotted rose snapper L. guttatus (Galaviz et al 2012) and Asian sea bass L. calcarifer (Srichanun et al 2013). The time sequence of gastric gland appearance and the maturation of the stomach vary among families, species and their reproductive guilds (Falk-Petersen 2005;Treviño et al 2011). In the present study, an increase in pepsinogen gene expression was first observed at 14-16 dph, while the increase in pepsin activity was first observed at 20-24 dph, coinciding with the formation of the stomach as an extension of the esophagus, showing a relationship between the synthesis of the precursor and the production of pepsin.…”
Section: Discussionmentioning
confidence: 89%
“…The above-mentioned differences may be linked to different larval and yolk-sac sizes (Kamler, 1992;Gisbert et al, 2000), but as well as different rearing conditions that might have affected the rate of yolk consumption and the onset of exogenous feeding. This period of mixed nutrition is of relevance with regard to larval performance as it may neutralize any potential deficit in nutrient provision before completion of yolk reserves, as well as serve as a temporary reserve of nutrients for the larva to withstand short periods of food deprivation (Treviño et al, 2011). The presence of a mixed nutrition stage might be an advantage for rearing P. punctifer larvae in ponds, as it would guarantee the successful transition to exogenous feeding of larvae or minimize the potential negative effects of a delayed time of first feeding (Gisbert and Williot, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the histological development of the digestive tract has been regularly used as a histological biomarker to assess the nutritional status of fish at early life stages of development . Although the basic mechanisms of organ and system development are similar among teleosts, there are considerable interspecific differences regarding their relative timing of differentiation, development and functionality during early ontogeny (Treviño et al, 2011). The timing of development of organ and physiological function is affected by the general life history and reproductive strategy of each species, especially in tropical species with fast development (Zambonino-Infante et al, 2008;Lazo et al, 2011).…”
mentioning
confidence: 99%
“…En peces teleósteos, los mecanismos de desarrollo del sistema digestivo son similares a pesar que existen considerables variaciones interespecíficas respecto al momento de la diferenciación y la funcionalidad de los diferentes órganos (Treviño et al, 2011), relacionadas principalmente con los procesos de digestión, absorción y asimilación de nutrientes (Dabrowski, 1984). Conocer los cambios que ocurren en el tracto digestivo durante el desarrollo ayuda a comprender la fisiología de la nutrición en larvas y a elegir el momento óptimo para iniciar la alimentación con raciones balanceadas, evitando altas mortalidades que ocurren cuando se suministran alimentos artificiales a ejemplares que no pueden asimilarlos (Person-Le Ruyet et al, 1993;Gisbert et al, 2004;Micale et al, 2006;Hamza et al, 2007).…”
Section: Introductionunclassified
“…En este sentido, los estudios histomorfológicos durante la ontogenia del sistema digestivo son una herramienta fundamental para evaluar la potencial utilidad de diferentes dietas para larvas, así como para dilucidar relaciones funcionales entre los diferentes órganos envueltos en los procesos digestivos (Hamza et al, 2007;Önal et al, 2008;Gisbert et al, 2009;Treviño et al, 2011).…”
Section: Introductionunclassified